Analisis Teknologi Quick Response (QR) Code dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas - M. Nuzulul Ulum; Amri Saputra; Lutfiah Holifah Balkis (Yayasan Al-Afif, 2025)
This study discusses the use of Quick Response (QR) Code technology in Islamic Religious Education (PAI) learning at senior high schools as an innovative strategy to improve the effectiveness and quality of the learning process. The study employs a literature review method by analyzing various national and international research related to the application of QR Codes in education. The findings show that integrating QR Codes enables teachers to present Islamic Religious Education materials such as Qur’anic verses, hadiths, explanatory videos, and discussion resources in a varied, interactive, and easily accessible way anytime and anywhere. The use of QR Code based media has been proven effective in enhancing students’ motivation, learning outcomes, creativity, and critical thinking skills. In addition, this technology supports character development and independent learning aligned with the demands of 21st-century education. Thus, implementing QR Codes in Islamic Religious Education learning has the potential to be a relevant, practical, and adaptive approach to enriching students’ learning experiences and supporting the achievement of Islamic education goals in the digital era.